DIAGNOSIS OF HEPATIC CAVERNOUS HEMANGIOMA USING TECHNETIUM-99M RED BLOOD CELL IMAGING - EKMAHACHAI, Molrudee; OJARUSPORN, Wannee; SIRIVANICHAI, Chusak; JITRAPITAKKUL, Sakonchai; BOONYAPRAPA, Sombut (The ASEAN Journal of Radiology, 2023)
Thirty-one patients with various focal hepatic lesions suspected of hepatic cavernous hemangiomas (HCHs) on liver ultrasonography(US) and/or computed tomography (CT) were evaluated by Technetium-99m red blood cell imagings. All patients were studied with blood- flow and sequential planar blood-pool images. Additional single-photon emission CT (SPECT) images were also performed in 19 patients. Twenty-five patients with scinti-graphic charac- teristic of HCH were diagnosed as HCH, 5 proven by angiography and 20 proven by main- taining a stable clinical course ranging from 6 to 24 months with the absence of any signs and symptoms of a liver malignancy, either primary or metastatic disease. All except 3 patients with a history of hepatitis B or C virus carrier had completely normal liver function tests. Six of 25 hemangioma patients had multiple lesions. Twenty-two cases of HCHs were clearly diagnosed by planar imagings and the other 3 patients needed SPECT imagings for diagnosis of HCHS. The remaining 6 patients, 4 had a final diagnosis as hepatoma proven by angiography and liver biopsy, and the other 2 patients were diagnosed as liver metastases proven by follow-up clinical course and liver US study.